#universitycrisis: The Impact of Social Media Type, Source, and Information on Student Responses Toward a University Crisis. (October 2014) - Snoeijers, Erik M.; Poels, Karolien; Nicolay, Colombine
Universities have every reason to avoid damaging their reputations through mismanaged crises. Moreover, universities have the moral duty to protect their students from harm by effective communication in a time of crisis. Social media have evolved into the fastest and most direct means to communicate with student populations. In this study, we experimentally tested the use of Twitter and Facebook as crisis communication media at a university. We further observed the effects of the communication source (university or dean) and the crisis information (instructing or adapting) on secondary communication by the students (e.g., sharing the message and leaving a reaction). The role of the dean as an information source seemed to incite action by students. We also found some counterintuitive effects, particularly with regard to the type of crisis information communicated on Facebook or Twitter, by the dean or the university.